Tropical Land Use Change and Soil Carbon: Implications for REDD Policies - Marin-Spiotta, Erika; Atkinson, Emily (Land Tenure Center, University of Wisconsin, 2010)
The release of soil carbon due to changes in land use can be a major source of greenhouse gases. This brief illustrates the distribution and scale of soil carbon in the humid tropics, an area with high concentrations of carbon soil stocks. The brief further analysis the impact that various land use changes have on these stocks, and the implications for climate change.
Keywords: climate change; land use change; land use; REDD policy; carbon sequestration; soil carbon; carbon